PERBEDAAN HARGA DIRI BERDASARKAN ORIENTASI SEKSUAL (HETEROSEKSUAL DAN HOMOSEKSUAL) DI YOGYAKARTA - Sri Putri Rahayu Z (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2020)
This study aims to determine differences in self-esteem based on sexual orientation by controlling perceived discrimination. The subjects of this study are heterosexual and homosexual people, where homosexuals are divided into two groups, namely gays and transvestites. The number of subjects in this study were 90 people consisting of 30 heterosexual people, 30 gay people and 30 transvestites. The instrument used for data retrieval is the scale of self-esteem, and the scale of perceived discrimination. Interviews and Focus Groub Discussions (FGD) were conducted to obtain qualitative data, which is used to discuss the results of quantitative analysis. The data in this study were analyzed by anacova analysis techniques. The results of this study indicate that there is no significant difference in self-esteem between sexual orientation and self-esteem with a value of F = 1.544 and p = 0.219 (p> 0.05) without controlling for the variable feeling discriminated against (perceived discrimination). The second analysis is done by analyzing perceived discrimination, showing that there is a significant difference in self-esteem with perceived discrimination, where the value of F = 5.314 and p = 0.024 (p <0.05). From the results of further analysis shows that there is a significant difference between self-esteem and sexual orientation by controlling feeling discriminated against (perceived discrimination) where the value of F = 3,639 and p = 0.030 (p <0.05).